FORMAÇÃO DE PROFESSORES: movimentos de criação? - Ferreira, Edith Maria Batista (2010)
The aim of the present study was to analyze approaches used by NUPECON Professors as to opposition to cultural replica process set forth by the continued education program of the county of São Luis, MA Brazil. The following issues are raised on the subject: how has NUPECON been extraofficially constituted for the training of teachers in the Municipal Education Network of Sao Luis, and how do the researching teachers resist to the cultural reproduction model imposed by the official teacher training Program? We hold the supposition that continuing education guided by the critique rationality model, with emphasis on the researching teacher, may contribute for the perception on ideological contents in the teaching practice resulting in more emancipating proposals. A qualitative study focusing on the oral history with nine participating subjects from NUPECON in the period of 2003 to 2008. A semistructured interview was utilized for data collecting, besides documental analysis, institutional reports, publications, intervention research projects, memorial and research report. Studies by Bourdieu, Foulcault, Certeau, Linhares, Garcia, Demo, among others, comprised the starting point so that we could question the cultural reproduction concepts, power relationships, resistance, approaches and researching teacher. As from the found clues we may infer that the true discussions aim at building a consensus with respect to government actions, and legitimate State reform, therefore, it is necessary to recognize the value of ideological argument as well as to inversions which may operate in pedagogical practice and thought. The training of researching teachers grounded on practical or technical rationality models favor the continuism and reinvigoration of neoliberal principles. The training of the researching teacher improves intellectual and pedagogical autonomy seized by the capitalist reasoning imbued in the education processes leading to more emancipating practices.